Development of the reading literacy questionnaire for EFL learners at primary schools - Li, Weilai; Kang, Shumin; Shao, Yanhong (Frontiers in Psychology, 2023)
Previous studies have indicated that there are a variety of factors influencing reading literacy assessment, including linguistic, cognitive, and affective factors, but little has been done on how to integrate these influential factors reasonably in a reading literacy instrument. As such, the purpose of this study is to develop and validate an English Reading Literacy Questionnaire (ERLQ) for English as foreign language (EFL) learners at the elementary level. The ERLQ was designed and revised through three rounds of validation with a sample of 784 pupils (Grades 3-6) in six primary schools from six provinces in China. Validity and reliability tests of the questionnaire were conducted with item anal-ysis, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), reliability test, and the analysis of criterion validity in SPSS 26.0 and AMOS 23.0. Results indicated that the revised ERLQ had high internal consistency, ranging from 0.729 to 0.823. The criterion validity of the ERLQ was supported by significant correlations to the Chinese Students’ English Rating Scale verified by the authoritative department, with a correlation coefficient of 0.871. The study shows that the revised questionnaire, with 3 dimensions of 14 items, has high reliability and validity, which can be used as an assessment instrument for the intended audience. It also suggests that modifications may be made for further use in other regions and countries, depending on the background information of the learners.